Mitigation of Insulin Resistance, Inflammation, Oxidative Stress, and Metabolic Abnormalities by Bavachalcone in High-Fat/High-Fructose Diet-Fed Rats - Yin, Jintang (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Obesity is defined by an excess of body fat, together with insulin resistance and dyslipidemia. These factors significantly elevate the risk of acquiring chronic disorders such as Diabetes Mellitus (DM), cardiovascular diseases, neurological disorders, etc. Objectives The goal of the current study was to evaluate bavachalcone's beneficial effects on insulin resistance and obesity in experimental rats fed a High-Fat and High-Fructose (HFa-HFr) diet. Materials and Methods The metabolic complications were induced in rats by HFa-HFr diet feeding for a period of 10 weeks and treated with bavachalcone from the 5th to the 10th weeks. The effects of bavachalcone on various parameters such as food and water consumption, body weight, insulin, blood glucose level, serum biochemical markers, liver oxidative stress markers, and proinflammatory cytokine levels were assessed after treatment. Additionally, a histopathological examination was conducted on the liver tissues. Results The findings showed that the rats fed with the HFa-HFr diet exhibited a notable elevation in blood glucose, insulin level, body weight, fat deposits, and liver marker enzyme activities. These changes were effectively mitigated by the bavachalcone treatment. Furthermore, the HFa-HFr diet resulted in elevated fat accumulation, oxidative stress, and inflammatory biomarker levels. In contrast, bavachalcone treatment successfully reduced insulin resistance, fat deposition, inflammatory, and oxidative stress conditions in the HFa-HFr diet-fed rats. Conclusion The results clearly showed that bavachalcone treatment successfully mitigated the HFa-HFr diet-caused metabolic abnormalities by reducing fat deposition and inflammatory and oxidative stress markers.
Keywords: Metabolic syndrome; Fatty liver; Bavachalcone; Insulin resistance; Inflammation